2015
DOI: 10.1080/08952833.2015.1030331
|View full text |Cite
|
Sign up to set email alerts
|

Connecting Trauma and Health for Mothers in the Child Welfare System

Abstract: This qualitative study focused on disadvantaged women in the child welfare system who have lost their parental rights. Utilizing a critical feminist and eco-developmental approach, the study was aimed at understanding how experiences of complex trauma influences parenting, health, and well-being. This sample consisted of 31 primarily ethnic minority, low income women. Findings identified how early and ongoing traumatic experiences (complex trauma) can contribute to health issues and inadequate functioning that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Birth parents of children in the statutory child protection services (CPS) 1 have disproportionally high rates of mental health problems, with significant trauma histories including sexual and physical abuse and neglect (Escobar-Chew et al, 2015). It is estimated that 22-80% parents in CPS also have a current mental health condition with the most common ones including mood, substance-, and stress-related disorders (McConnell et al, 2000;O'Donnell et al, 2015;Riihimäki, 2015;Stromwall et al, 2008;Westad & McConnell, 2012).…”
mentioning
confidence: 99%
“…Birth parents of children in the statutory child protection services (CPS) 1 have disproportionally high rates of mental health problems, with significant trauma histories including sexual and physical abuse and neglect (Escobar-Chew et al, 2015). It is estimated that 22-80% parents in CPS also have a current mental health condition with the most common ones including mood, substance-, and stress-related disorders (McConnell et al, 2000;O'Donnell et al, 2015;Riihimäki, 2015;Stromwall et al, 2008;Westad & McConnell, 2012).…”
mentioning
confidence: 99%
“…It has been reported that there are disproportionately high rates of birthparents involved in statutory child protection services that suffer from mental health problems, specifically trauma histories of abuse and neglect (Escobar‐Chew et al, 2015). Research suggests that many parents involved in child protection services are affected by PTSD, specifically C‐PTSD, with presentations of multiple, childhood and interpersonal trauma (Karatzias et al, 2017; Suomi et al, 2021).…”
Section: Trauma: Birthparents and Young Peoplementioning
confidence: 99%